IMPLEMENTATION OF EVOLUTION STRATEGIES (ES) ALGORITHM TO OPTIMIZATION LOVEBIRD FEED COMPOSITION - Rizki, Agung Mustika; Mahmudy, Wayan Firdaus; Yuliastuti, Gusti Eka (Scientific Journal of Informatics, 2017)
Lovebird current society, especially popular among bird lovers. Some people began to try to develop the cultivation of these birds. In the cultivation process to consider the composition of feed to produce a quality bird. Determining the feed is not easy because it must consider the cost and need for vitamin Lovebird. This problem can be solved by the algorithm Evolution Strategies (ES). Based on test results obtained optimal fitness value of 0.3125 using a population size of 100 and optimal fitness value of 0.3267 in the generation of 1400.